Lecture IV: Intuitive music (IT): And Questions and answers on intuitive music - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 2007)
Lecture IV: Intuitive Music ( IT ) and Questions and Answers on Intuitive Music given on February 15th1972 at the Institute of Contemporary Arts in London. This is the second part of the lecture originallyentitled Live Electronic Music and Intuitive Music ( see Lecture II ).